2015
DOI: 10.1590/0103-8478cr20140414
|View full text |Cite
|
Sign up to set email alerts
|

Adaptabilidade e estabilidade de genótipos eretos de amendoim cultivados nas regiões Nordeste e Centro-Oeste

Abstract: O presente trabalho teve por objetivo estimar a estabilidade e a adaptabilidade de oito genótipos de amendoim ereto e comparar os modelos de análise de EBERHART & RUSSELL (1966), WRICKE (1965) e LIN & BINNS (1988), baseando-se em dados de produtividade de vagens e sementes. Os genótipos de amendoim foram avaliados em 14 ambientes situados nas Regiões Nordeste e Centro-Oeste, durante os anos de 2006 a 2011, sob o delineamento de blocos ao acaso com cinco repetições. Verificou-se que, entre os três métod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
8
0
3
Order By: Relevance
“…The existing differences in results among different methods occurs in most studies. For some authors, it brings more trust to indicate if the same results were found in different methods rather than just one (MARQUES et al, 2011;PELÚZIO et al, 2008;VASCONCELOS et al, 2015). Therefore, it is advisable to use methodologies for different statistical classifications, as used in this study.…”
Section: It Is Verified Inmentioning
confidence: 87%
“…The existing differences in results among different methods occurs in most studies. For some authors, it brings more trust to indicate if the same results were found in different methods rather than just one (MARQUES et al, 2011;PELÚZIO et al, 2008;VASCONCELOS et al, 2015). Therefore, it is advisable to use methodologies for different statistical classifications, as used in this study.…”
Section: It Is Verified Inmentioning
confidence: 87%
“…Two earliness and upright peanut genotypes (BR1 and L7 Bege) were used in assays. BR 1 is a cultivar developed by Peanut Breeding Program, coordinated by Brazilian Company of Agricultural Research (Embrapa) and recommended to semiarid region (Santos et al, 2010) and L7 Bege is a top line, derived from a drought tolerant cultivar (Senegal 55 437), with broad adaptability to Northeast region (Vasconcelos et al, 2015).…”
Section: Genetic Resources and Rhizobia Growthmentioning
confidence: 99%
“…BR 1 (earliness, Valencia type) and found gains ranging from 6 to 15% to number of peg, 4 to 17% to number of pod/plant and 3 to 17% to 100 pod weight. Vasconcelos et al (2015) estimated the stability and adaptation of runner genotypes to semiarid environment during three years, including LViPE-06, LGoPE-06, BRS Pérola Branca, Florunner and IAC Caiapó. The authors found best results to BRS Pérola Branca and LViPE-06, while LGoPE-06 showed excellent results to pod production, but was highly dependent upon favorable environments.…”
Section: Resultsmentioning
confidence: 99%
“…The Brazilian Company of Agricultural Research (EMBRAPA) coordinates a robust peanut breeding program targeted to oil and food markets, focusing on the development of Valencia and Runner cultivars adapted to environments with water restriction . Annually EMBRAPA has invested a large sum in generation of populations derived from interspecific genotypes in order to combine yield and early maturity, concentrating efforts in environments with semiarid climates (Luz et al, 2014;Vasconcelos et al, 2015;Pereira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%